The Tax Evasion of Income Tax in SMEs of the Hardware Stores of the Province of Sullana, Piura - Jurado-Rosas, Adolfo Antenor (2020)
The objective of this research is to determine and describe the tax evasion of income tax in the SMEs of the Hardware Stores of the province of Sullana from the high rate of tax evasion that is evidenced in the country and the different modalities that exist to carry carry out these illicit actions. The present research work was descriptive in nature, with a cross-sectional quantitative approach, the type of research was non-experimental because it was carried out without deliberately manipulating the variables, the phenomenon was observed as it is within its context. Obtaining as results the identification that within the tax doctrine referring to tax evasion with a high rate of informality, 25 % do so, while 75 % do not. Since they are aware of the consequences it can cause, it is therefore recommended that the corresponding guidance be taken so that tax laws are not violated. Coming to the conclusion that companies do not yet accept the issuance of electronic vouchers, either due to the lack of information or the inability to do so since this change greatly influences the work of the company, since it can be make an investment for the correct implementation of electronic invoicing.